IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA KELAS VI SD - Ricky Avandra; Desyandri (STKIP Subang, 2022)
The background of this research is the low skills of students in learning so that they do not develop the potential and skills possessed by students, especially the critical thinking skills of Class VI elementary school students. The purpose of this research is to improve the critical thinking skills of grade VI elementary school students. One type of learning that can meet student learning needs by paying attention to student readiness, interests and learning profiles is Differentiated Learning. Therefore it is necessary to improve science learning through the application of Differentiated learning. This research method is descriptive qualitative using classroom action research carried out in two cycles consisting of planning, implementation, observation, and reflection stages. The data collection tool uses observation sheets and test questions. The results of the study show that the application of differentiated learning can improve students' critical thinking skills. This can be seen from the category of student skills in cycle I meeting 1 good category 30% and meeting two 60% then increasing in cycle II meeting 1 which is 80% and increasing 95% in meeting II. Based on the results of the analysis on the actions of cycles I and II, it can be seen that there is an increase in students' critical thinking skills from the actions of cycle I, namely 40% in the good category increasing to 87.5% in cycle II.